Student Perceptions of a Hands-on Practicum to Supplement an Online eHealth Course - Edirippulige, Sisira; Smith, Anthony C; Armfield, Nigel R; Bensink, Mark; Wootton, Richard (JMIR Publications, 2012)
BackgroundSince 2000, the Centre for Online Health (COH) at The University of Queensland has offered a range of online eHealth courses at the undergraduate and postgraduate level. While online learning has a number of advantages, in some domains, it can present some challenges to the development of practical skills and experience. ObjectiveTo assess students' perceptions of the value of an eHealth practicum. MethodsTo supplement our online learning program, we introduced an eHealth practicum component that aimed to expose students to a range of clinically relevant learning experiences. Subsequently, by means of a questionnaire, student perceptions of the practicum were assessed. ResultsOver two semesters, a total of 66 students participated in the eHealth practicum, and questionnaire responses were very positive. The majority of students agreed that the practicum allowed them to gain necessary skills in eHealth applications (59%) and provided them with an opportunity to explore ways of using different eHealth tools for the delivery of health care at a distance (62%). ConclusionsThe study shows that a practical component in eHealth teaching was well received by students. While online teaching is appropriate for providing knowledge, the opportunity to develop practical skills may encourage students to use eHealth techniques in their future practices.